Papillon Lefevre Syndrome - M Lotfazar (Tehran University of Medical Sciences, 2003)
Papillon Lefevre Syndrome (PLS) is a rare recessive autosomal disease, which is associated with palm and sole hyperkeratosis and early periodontium break down of deciduouse and permanent dentition. In the differential diagnosis of PLS, congenital form of palm and sole hyperkeratosis should be considered.Recently, mutation in catepesin C gene has been recognized as a genetic basis for PLS disease. In this disease, complete lack of catepesin C enzyme activity, due to the mutations on both allels, are observed. Actinobacillous actinomycetemcomitans (A.a) bacteria are presented as the main periodontal pathogene in PLS disease. The treatment results have been contradictory and no agreement has been obtained in this regard. Elimination of A.a bacteria and administration of synthetic retinoids are reported as a suitable treatment.